If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(2x+17)+(6x-43)=180
We move all terms to the left:
x+(2x+17)+(6x-43)-(180)=0
We get rid of parentheses
x+2x+6x+17-43-180=0
We add all the numbers together, and all the variables
9x-206=0
We move all terms containing x to the left, all other terms to the right
9x=206
x=206/9
x=22+8/9
| 8(x+6)-3x=68 | | 5(5)=7x-22/4 | | -x+3-5=-4 | | -y+5=19 | | 180=(4x-14) | | 7q-1=7q+3 | | (19x+30)+x=90 | | 74/5=v | | 4x16=x-10≥-4 | | 6x+4+8x+4+2x+11=180 | | -a+3=2a-3a | | 47=4x | | d=-3+1/2 | | (2x)/13-6=4 | | 3w-4=2w-10 | | 6x+3=-8+2x+19 | | 4x+4(x-3)=36 | | 2u-3=2u | | -2(-x-7)+3=19 | | n-2/5=3/10 | | -9b-1=89 | | 4x+57+17+90=180 | | 4.82-(-8.6)=b | | 36x=4x²-4x³ | | -2(3x+1)=40 | | 7.2x-1=-143 | | –8+9m=5m | | x/4=2x(x-3)/3 | | 8x+6=10 | | 4x=2+2*1 | | 14+5=-5x-6(-3- | | 4y+8=3y+2 |